Composition of the Lipids of the Sphagnum and Cotton Grass Peats in the Forest Steppe and Southern and Middle Taigas of West Siberia; Solid Fuel Chemistry; Vol. 51, iss. 4 - Serebrennikova O. V. Olga Viktorovna; Strelnikova E. B. Evgeniya; Russkikh I. V. Irina Vladimirovna; Duchko M. A. Mariya Aleksandrovna (2017, 2017)
Title screen